2008
DOI: 10.1111/j.1464-410x.2008.07706.x
|View full text |Cite
|
Sign up to set email alerts
|

The combination of docetaxel and the somatostatin analogue lanreotide on androgen‐independent docetaxel‐resistant prostate cancer: experimental data

Abstract: OBJECTIVE To evaluate the effects of the association between docetaxel and the somatostatin analogue lanreotide on the androgen‐independent prostate cancer cell line PC3, either sensitive or made resistant to docetaxel (PC3R), as new drugs and new combinations have promising clinical activity in hormone‐refractory prostate cancer. MATERIALS AND METHODS We examined the effect of docetaxel and lanreotide on cell proliferation, with analysis of the mitogen‐activated protein kinase pathway and expression of cell‐c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 20 publications
3
27
0
Order By: Relevance
“…In contrast, the cytotoxic radical and the carrier protein, administered separately, were ineffective and toxic (68). In line with these data, a recent in vitro study reported that lanreotide could interact with docetaxel in HRPCa cells, with possible explanatory mechanisms involving the regulation of the interaction of P-glycoprotein-mediated docetaxel through lanreotide (69). This latter evidence was corroborate by the same authors which also demonstrated that octreotide and docetaxel combination increase HRPCa cell death through cell cycle regulation and induction of apoptosis (70).…”
Section: Somatostatin Analogues and Prostate Cancersupporting
confidence: 79%
“…In contrast, the cytotoxic radical and the carrier protein, administered separately, were ineffective and toxic (68). In line with these data, a recent in vitro study reported that lanreotide could interact with docetaxel in HRPCa cells, with possible explanatory mechanisms involving the regulation of the interaction of P-glycoprotein-mediated docetaxel through lanreotide (69). This latter evidence was corroborate by the same authors which also demonstrated that octreotide and docetaxel combination increase HRPCa cell death through cell cycle regulation and induction of apoptosis (70).…”
Section: Somatostatin Analogues and Prostate Cancersupporting
confidence: 79%
“…Interestingly, other PC3-derived docetaxel-resistant cell lines have been reported with widely varying degrees of resistance. The reported resistance factor ranged from 4 to 400 nmol/L (20). The LDocR cells used in our report therefore represent a moderately resistant derived cell line, with just a >10-fold increase in the GI 50 value for docetaxel along with increased MDR1 activity (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…We first established the docetaxel-resistant PC3 (PC3R) using the method evaluated by the previous report [11] . PC3 cells were made resistant to docetaxel by culturing them under continuous exposure to docetaxel (10 nmol/L) for 30 days.…”
Section: Exposure To Docetaxel and Ic 50 Values Of Pc3wt And Pc3r Cellsmentioning
confidence: 99%